Isolation of a novel alginate lyase‐producing Bacillus litoralis strain and its potential to ferment Sargassum horneri for biofertilizer - Mingpeng Wang (MicrobiologyOpen, 2016)
Abstract Algae have long been used to augment plant productivity through their beneficial effects. Alginate oligosaccharide is believed to be one of the important components to enhance growth and crop yield. In this study, we isolated and characterized a Bacillus litoralis strain, named Bacillus M3, from decayed kelps. We further demonstrated that the M3 strain could secrete alginate lyase to degrade alginate. The crude enzyme exhibited the highest activity (33.74 U/mg) at pH 7.0 and 50°C. The M3 strain was also able to ferment the brown alga Sargassum horneri. Fermentation results revealed that a fermentation period of 8–12 hr was the best harvest time with the highest level of alginate oligosaccharides. Plant growth assay showed that the seaweed fermentation extract had an obvious promotion effect on root and seedling growth of Lycopersicon eseulentum L. Our results suggest that fermentation extract of Sargassum horneri by the novel strain of Bacillus litoralis M3 has significant development potential for biofertilizer production and agriculture application.